Caracterización de los pacientes con intento de suicidio atendidos en un hospital pediátrico - Eraso Osejo, Jimena; Chaves Camayo, Dalila; Gámez Patiño, Paula Alexandra (Universidad y Salud, 2008)
An epidemiological, observational, descriptive, retrospective study was carried out in the Children’s Hospital Los Angeles at Pasto with the aim of characterizing the suicide attempt cases received by this hospital from January to December, 2007. The epidemiological charts of the events and the medical records were analyzed. Additionally, a semi structured interview was applied to the guardians of the teenagers after they were discharged from the hospital. It was identified that the most of suicide cases one presents in famele teenagers between 14 - 15 years old and lived in urban areas. In every case the chosen method was intoxication with insecticides and medication. The triggering factors were related to family and personal conflicts. Also, situations like depression were diagnosed by psychology and psychiatry services in a high percentage of the population (57% and 76%). The results lead to conclude the importance of psychosocial interventions on teenage populations in areas like family and social relationships, and the relevance of early detection and attention to mental health from a psychological and psychiatric viewpoint.